1999
DOI: 10.1002/(sici)1521-4109(199903)11:3<156::aid-elan156>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of a Capacitive Biosensor for Direct Detection of DNA Hybridization

Abstract: This preliminary study was performed to prove the feasibility of a direct capacitive DNA biosensor for detection of nucleic acids. Two different methods for immobilization of the oligonucleotide probes were used. The ®rst type of sensor was composed of a gold rod with a self-assembled monolayer of a 26-base long oligonucleotide probe, modi®ed with an SH-group at the 5 H -end. Coverage studies showed that only around 20% of the surface was covered, probably due to the bulky nature of the probes. Hybridization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(144 citation statements)
references
References 23 publications
5
127
1
1
Order By: Relevance
“…In 1998 similar results were reported for IL-2, and even more impressive results for IL-6, though the detection limits were not specified [149]. The same investigators later constructed a DNA biosensor based on the same principle, and reported a detection limit of 0.2 aM for a 179mer ssDNA target using 26mer and 8mer oligonucleotide probes [188]. They used a target much larger than the probe, but a still-impressive 1 -5 aM limit of detection is expected for identical-length targets.…”
Section: Potentiostatic Stepmentioning
confidence: 73%
“…In 1998 similar results were reported for IL-2, and even more impressive results for IL-6, though the detection limits were not specified [149]. The same investigators later constructed a DNA biosensor based on the same principle, and reported a detection limit of 0.2 aM for a 179mer ssDNA target using 26mer and 8mer oligonucleotide probes [188]. They used a target much larger than the probe, but a still-impressive 1 -5 aM limit of detection is expected for identical-length targets.…”
Section: Potentiostatic Stepmentioning
confidence: 73%
“…The carbodiimide covalent coupling of a 8-mer oligonucleotide to a previously self-assembled monolayer of cysteamine was described by Johansson and co-workers (Berggren et al, 1999).…”
Section: Carbodiimide Covalent Coupling To Preformed Self-assembled Mmentioning
confidence: 99%
“…Johansson's group demonstrated that the decrease in capacitance of a probe-modified gold electrode, accrued from the hybridisation to the complementary strand and the corresponding displacement of solvent molecules from the surface, can be used for monitoring with high sensitivity and speed the hybridisation event (Berggren et al, 1999). In hybridisation studies performed in a flow-through cell, as few as 25 molecules of single-stranded, 179 bp cytomegalovirus target sequence could be detected.…”
Section: Label-free Approachmentioning
confidence: 99%
“…The large differences in capacitance measurements arising from the interfacial properties of ss-and dsDNAs have been shown to recognize DNA hybridization (1,27,28). Recently, a three-component ODN system on a gold electrode was used to detect specific DNA sequences by Faradaic impedance spectroscopy (29).…”
Section: Dn Na a C Co On Nd Du Uc Ct Ti Iv Vi It Ty Ymentioning
confidence: 99%